INTRODUCING THE GENDER PERSPECTIVE IN PSYCHOLOGICAL RESEARCH ABOUT GENDER VIOLENCE - Ferrer Pérez, Victoria A.; Bosch Fiol, Esperanza (Anales de Psicología / Annals of Psychology, 2005)
Traditional psychology has considered itself to be a neutral, objective and independent science. Nowadays many voices question this objectivity and independence, and propose alternative solutions to its traditional androcentrism. These solutions include, for example, methodological modifications (in samples, in instruments of measurement, etc.) (Barberá, 1998; Hyde, 1995), and, definitely, the incorporation of the gender perspective. In this article some methodological problems in the psychological current investigation on gender violence (and, specifically, on domestic violence) are analysed and some alternatives situation are proposed.